KEARIFAN LOKAL: TRADISI SEDEKAH BEDUSUN DI DESA PAYABAKAL KECAMATAN GELUMBANG KABUPATEN MUARA ENIM - Alauwiyah, Fatimah; Wijaya, Tomy (Historia, 2025)
This research seeks to explore the practice of Sedekah Bedusun through a combination of literature analysis, observational methods, and interviews with knowledgeable individuals, all employing a qualitative descriptive approach. The literature analysis provides insight into the historical background, cultural values, and social implications surrounding this practice. In contrast, interviews offer a deeper perspective on Sedekah Bedusun from the viewpoint of the local community. The primary goal of this study is to elucidate the significance and impact of Sedekah Bedusun in fostering social relationships and upholding traditional values. Findings from the research reveal that Sedekah Bedusun serves not only as a source of economic support for those in need but also as a vital means of enhancing social solidarity, reinforcing cultural identity, and ensuring the continuity of traditional values within the community. Overall, this research makes a substantial contribution to our understanding of Sedekah Bedusun as a relevant social and cultural phenomenon, particularly in the context of rural communities.